Método canguru e o estado nutricional do prematuro – uma revisão da literatura - AUGUSTO, Bárbara Vitória Monteiro Reis (2023)
The Kangaroo Method (KM) is a model of humanized care in which minimally invasive practices are used through skin-to-skin contact between the baby and the mother or other family members. Objectives: To investigate the literature on the Kangaroo Method and its impacts on the nutritional status of preterm infants. Methods: This was a qualitative study, using the norms of a bibliographic review. The period of collection by electronic means published was from 2017 to 2022. Results: The physiological development of the premature baby may be directly associated with the prevalence of the Kangaroo Method to minimize invasive procedures for the baby. Breastfeeding during the Kangaroo Method is a positive factor for the contribution of its quality and influences its exclusivity. In addition, skin-to-skin contact makes the affective bond stronger and thus helps in the mother-baby relationship. Maternal complications are breast lesions and musculoskeletal pain. The multiprofessional team is essential for the evolution of the kangaroo method and for the knowledge of family members about the correct method. Conclusion: The kangaroo method is a positive factor for preterm development. As it is a light treatment technology, non-invasive, easy to perform and economical, it should be encouraged.